تطوير المواد التعليمية لتعليم القواعد الإعرابية باستخدام Wix Web لترقية كفاءة إعراب الجمل لطلاب قسم تعليم اللغة العربية جامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج: Pengembangan Bahan Ajar Aturan Sintaksis Menggunakan Wix Web untuk Meningkatkan Efisiensi Sintaksis Kalimat Bagi Mahasiswa Jurusan Pendidikan Bahasa Arab UIN Maulana Malik Ibrahim Malang - Lailatul Maghfiro; Ahmad Yani; Wildana Wargadinata (Shaut al Arabiyyah, 2022)
The study of Nahwu includes several important studies, such as the study of I’rab. Basically, the students of State Islamic University Maulana Malik Ibrahim Malang are able to understand Nahwu, yet they are not easy to understand I’rab. They are difficult to learn about it so that they do not focus on the process of learning. It happens because of the lack of examples used in the way of giving I’rab in sentences. Therefore, the researcher has initiative to create a book that explain about I’rab so that the students are able to learn independently. The researchers used a qualitative and quantitative approach and then used the research and development method. In product development, researchers used the theory of Borg and Gall. The results of the research are: The preparation of the I'rab book based on independent learning through several stages, namely a basic study to find out the problems and needs. Then design the materials, methods, media and learning objectives. Then the development of independent learning-based books, as for the book components: cover, use, opening material, materials, examples, references, and compilation biographies, then continued with validity. from the experts. The use of I'rab books based on self-study is considered effective.From this statement, it can be said that the grammar learning media using the Wix web is a learning media that helps students to more easily understand the study of nahwu science in depth because this media is arranged according to the chapters written in the aljurumiyah book